(untitled) (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Eclampsia poses a global threat in terms of feto-maternal morbidity and mortality and all medical practitioners fear the ailment. It is one of the major causes behind preventable maternal death. Etio-pathogenesis of the disease condition is ambiguous and is considered to be multi-factorial. This study was done to analyze cases of eclampsia in relation to maternal and fetal outcomes at a tertiary level care hospital. Materials and Methods: A descriptive cross-sectional observational study was carried out in patients developing eclampsia over a period of five years starting from July 2011 to June 2016 at National Medical College and Teaching Hospital, Birgunj. Relevant data were collected from the statistics section of hospital reviewing the case sheets. Results: There were 291 cases of eclampsia out of 16,445 deliveries and prevalence of eclampsia was calculated to be 1.77%. Fourty-five percent of eclamptic women had age less than 20 years and two-third was primigravida. Approximately 84% of women were unbooked. Antepartum eclampsia was observed in 78.8% followed by postpartum eclampsia (14.8%) and intrapartum eclampsia (6.5%). At the time of admission systolic blood pressure more than 140 mmHg and diastolic blood pressure more than 90 mmHg were noted in 79% and 92.1% cases respectively. Caesarean section was the preferred mode of delivery and was performed in 62.9% cases. ICU admission was required in 35.7% and remaining cases were managed in general/eclampsia ward. Renal failure was the most common cause of maternal mortality seen in 29.4%. Still birth was noted in 13.4%. Conclusion: Institutional obstetric patients are gradually facing eclampsia as prime cause of maternal death and unfortunately most of the cases are primigravid at younger age. All health care professionals should be proficient to manage eclamptic women instantaneously. Key words: Eclampsia; Fetal Mortality; Maternal Mortality; Pre-Eclampsia